Value dynamics and interpersonal tension among astronauts during International Space Station missions - Gro Mjeldheim Sandal; Nathan Smith (PLoS ONE, 2026)
Astronauts’ ability to maintain motivation over extended periods is crucial for space mission success. This paper examines how motivational goals (personal values) change during space missions and explores the associations between perceived value congruence and intra-crew tension among astronauts staying 4–7 months at the International Space Station. Twelve astronauts regularly completed the Crew Values Questionnaire (CVQ) package, assessing personal values, perceived value congruence of crew members, and tension attributed to perceived value incongruence. Overall, they rated their values, particularly universalism, benevolence, and tradition, as highly concordant. Temporal analyses showed that scores for hedonism and power increased early in missions and declined later, while benevolence and security decreased and rose again towards the end and into post-mission. Perceived value-congruence followed similar trajectories, with differences in achievement, power, and benevolence decreasing and then increasing across mission phases. Multilevel modeling showed that perceived incongruence in seven out of eight personal values significantly predicted interpersonal tension. In conclusion, in-mission adjustments of value priorities may have helped astronauts sustain motivation, but these shifts could also influence crew dynamics. Pre-mission training and in-flight support should target shifts in motivational sources and manage interpersonal tensions from value diversity to prevent adverse outcomes and leverage crew heterogeneity.